ChemInform Abstract: Lewis Acid Mediated Vinyl‐Transfer Reaction of Alkynes to N‐Alkylimines by Using the N‐Alkyl Residue as a Sacrificial Hydrogen Donor. Issue 13 (1st April 2014) - Malakar, Chandi C.; Stas, Sara; Herrebout, Wouter; Abbaspour Tehrani, Kourosch
Abstract A wide variety of allylic amines from imines and alkynes are synthesized by using In(O‐Tf)3 as Lewis acid.